Rapa whelk (Rapana venosa) trails from the Black Sea Romanian Inner Shelf (SE Mangalia) (Geo-Eco-Marina, 2021)
The trail of Rapana from the Black Sea inner shelf, discussed in this paper, can be used to identify possible traces of this species in more recent deposits than the Upper Miocene. Traces of this type betray the presence of the invasive Rapana gastropod, when the animal cannot be observed directly, thus constituting the indirect evidence of the intruder‘s presence in new marine domains, conquered by active or inactive migration.
Keywords: neoichnology; trail; Gastropoda; invasive species; Rapana venosa; Black Sea; Romanian inner shelf